Development of coupled DDA-SPH method for dynamic modelling of interaction problems between rock structure and soil. (October 2021) - Peng, Xinyan; Chen, Guangqi; Fu, Haiying; Yu, Pengcheng; Zhang, Yingbin; Tang, Zhicheng; Zheng, Lu; Wang, Wei
Abstract: Simulation of interaction problems between rock structure and soil is a challengeable subject. It involves a coupled system that considers the behaviors of both rock structure and soil, together with interaction between them. Discontinuous deformation analysis (DDA) is suitable for analyzing a blocky system, such as rock or flexible structure. On the other hand, smoothed particle hydrodynamics (SPH) is appropriate for studying flow-like behavior of soil after implementing a proper constitutive model. A coupling scheme that bridges DDA and SPH can take advantages of both methods. Therefore, a numerical method for such interaction problems using DDA and SPH is developed, in which a Drucker-Prager elasto-plastic soil constitutive model is incorporated. In the developed method, the interaction between SPH particle and DDA block is idealized through a new spring-dashpot contact model with the Mohr-Coulomb failure criterion used. Several numerical examples are studied, and satisfactory agreements between the simulation results and the experimental data or other available simulated results are obtained, suggesting the correctness of the developed method. Further, the developed method is applied to study influence of backfill on a masonry arch bridge. Conclusively, this coupled DDA-SPH method provides a potential numerical approach for studying interaction problems between rock structure and soil. Highlights: Developed coupled DDA-SPH method for interaction problems between rock structure and soil. Incorporated a Drucker-Prager elasto-plastic constitutive model for soil in coupled DDA-SPH method. Proposed a new spring-dashpot contact model for the coupling scheme between SPH particles and DDA blocks. Checked validity and feasibility of the proposed method by various examples.